Answer:
Step-by-step explanation:
To find g-¹( 2) we must first find g-¹(x)
To find g-¹(x) equate g(x) to y
That's
y = g(x)
We have
y = - 2x + 7
Now interchange the terms that's x becomes y and y becomes x
We have
x = - 2y + 7
Make y the subject in order to find g-¹(x)
Move 7 to the left side of the equation
- 2y = x - 7
Multiply both sides by - 1
We have
2y = 7 - x
Divide both sides by 2 to make y stand alone
That's
So we have
Now to find g-¹(- 2) substitute the value of x that's - 2 into the expression
We have
We have the final answer as
Hope this helps you